Does War Foster Cooperation or Parochialism? Evidence from a Natural Experiment among Turkish Conscripts - Arzu Kıbrıs; Resul Cesur (Institute of Labor Economics (IZA), 2023)
Exploiting a natural experiment and an innovative survey design, we study the social and political legacies of armed conflict exposure (ACE) among Turkish conscripts. Our empirical framework identifies the causal impact and isolates the mediating pathways for the average male randomly picked from the population. Contrary to the arguments that war fosters prosociality and posttraumatic growth, we find little evidence that ACE promotes cooperative behaviors. Instead, we document evidence that ACE fosters parochialism, measured by increased opposition to peaceful means of conflict resolution, animosity towards minorities, and the tendency to support right-wing political parties. As the study design eliminates the need for social insurance, security concerns, and community-level paradigm shifts, and our analysis rules out labor market outcomes, human capital formation, and military socialization from the list of the usual suspects, we conclude that, in the absence of favorable neoclassical mediating pathways boosting demand for cohesion, violence exposure, in and of itself, is not sufficient foster cooperative behaviors but promotes parochialism. Further analyses show war-driven grievances, the normalization of violence in everyday life, and changes in parochial norms and preferences as the transmitting pathways.
Keywords: D74; O17; Z13; 330; war exposure; cooperation; parochialism; conflict resolution; grievances; conflict trap